The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.msec.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized dermis–polymer complex provides a platform for soft-to-hard tissue interfaces

Abstract: To develop a soft-to-hard tissue interface, we made a decellularized dermis/poly(methyl methacrylate) (PMMA) complex by soaking the decellularized dermis in methyl methacrylate (MMA) and an initiator, and then polymerizing the MMA. The decellularized tissue was chosen because of its good biocompatibility and the easiness of suturing it, and MMA because of its hard tissue compatibility and wide use in the biomedical field. The MMA filled the cavities in the dermis and polymerized within 10 min. No leaking or po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 35 publications
2
19
0
2
Order By: Relevance
“…The DD was prepared using the high‐pressure method that we previously reported . The dermis was placed into polyethylene bags containing PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DD was prepared using the high‐pressure method that we previously reported . The dermis was placed into polyethylene bags containing PBS.…”
Section: Methodsmentioning
confidence: 99%
“…The fundamental idea is based on the articles by Nakabayashi research group, where they showed that the methyl methacrylate (MMA) can absorb the tissue and be polymerized . We previously reported a complex of decellularized dermis (DD) and PMMA for use as a tissue interface with similar methods . A tissue interface is a material that is placed at the interfaces between multiple types of tissue with different physical properties to facilitate regeneration of the damaged zone .…”
mentioning
confidence: 99%
“…Decellularized matrices are characterized by a low immunogenic potential and adequate mechanical properties (both on the macro-and micron-scale). Furthermore, they provide cells with natural adhesive ligands and open porosity, which make them perfect candidates to assess cell migration and invasion in vitro (DeQuach et al, 2011;Matsushima et al, 2014). Despite these unique features, the use of decellularized matrices requires that the complex and delicate chemical/physical processes that lead to the decellularization must be carefully undertaken to not affect the outcome of the subsequent cell cultures (Song and Ott, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hard tissue applications include interactions of these materials with bones and teeth, and soft tissue applications may involve interactions of materials with human tissues such as blood and blood vessels [4][5][6]. These materials are used to treat, repair, or alter diseased tissues and organs to enhance functionality [7][8][9]. At present, most studies involving biomedical materials are focused on developing biodegradable materials based on polylactic acid (PLA), poly(hydroxyalkanoate) (PHA), and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) [10][11][12].…”
Section: Introductionmentioning
confidence: 99%